Exploring Zinc and Boron Chemo-Priming Effects on Low-Vigour Seed Germination and Seedling Establishment of Sunflower (Helianthus annuus L.) - Negar Ebrahim Pour Mokhtari; Ferhat Kızılgeçi; Raees Ahmed; Muhammad Aamir Iqbal (Turkish Journal of Agriculture: Food Science and Technology)
Poor germination and suboptimal seedling growth constitute as prime factors in lowering the achene yield and seed oil content of sunflower (Helianthus annuus L.), while chemo-priming with micronutrients might serve as a biological viable strategy provided source and dose optimization are performed. A trial was executed to appraise the comparative impact of seed priming with different doses of micronutrients like boron (B) and zinc (Zn) on sunflower germination and seedling growth traits of sunflower. The experiment was comprised of six treatments of B (0, 0.2, 0.4, 0.8, 1.6, 3.20 ppm) and Zn (0, 4, 8, 12, 16 and 20 mM) each, while seed germination, root and seedling growth related traits were taken as experimental variables. The results revealed that all treatments remained ineffective regarding seed germination and seed vigour of sunflower, while B and Zn doses of 0.2 ppm and 12 mM respectively, enhanced seedling emergence rate and vigour. The Zn (8 mM) significantly improved root length along with their fresh and dry weights, while all doses of B imparted antagonistic effects on root attributes. Likewise, Zn (8 mM) remained superior for shoot length, fresh and dry weights, while higher doses of B remained contra-productive for shoot growth of sunflower.